(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article empirically investigates the psychological factors and the conditions of manifestation that cause mobile communication dependency in adolescents. The socio-psychological mechanisms of mobile communication dependency in adolescents are identified, and necessary practical recommendations have been developed.